Solving systems of coupled nonlinear Atangana–Baleanu-type fractional differential equations - Hasanen A. Hammad; Mohra Zayed (Boundary Value Problems, 2022)
Abstract In this work, we investigate two types of boundary value problems for a system of coupled Atangana–Baleanu-type fractional differential equations with nonlocal boundary conditions. The fractional derivatives are applied to serve as a nonlocal and nonsingular kernel. The existence and uniqueness of solutions for proposed problems using Krasnoselskii’s and Banach’s fixed-point approaches are established. Moreover, nonlinear analysis is used to build the Ulam–Hyers stability theory. Subsequently, we discuss two compelling examples to demonstrate the utility of our study.